2013
DOI: 10.1136/gutjnl-2013-304907.168
|View full text |Cite
|
Sign up to set email alerts
|

PTU-076 Diagnostic Potential of Volatile Organic Compounds as Faecal Biomarkers in Inflammatory Bowel Disease

Abstract: Introduction VOCs can be utilised as non invasive biomarkers for gastrointestinal diseases such as IBD, as changes in VOCs reflect internal metabolical and pathological processes. Methods Patients were recruited from outpatients with proven Crohn’s disease(CD N = 41), ulcerative colitis(UC N = 49), IBS(N = 30) and healthy volunteers(N = 47). Disease activity was recorded using Harvey-Bradshaw index(HBI) in CD and simple clinical colitis activity index(SCCAI) in UC. Faecal headspace gas was sampled with SPME … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Previous work using sophisticated and expensive analytical equipment has shown that the VOC analysis approach for IBD and IBS diagnosis is a promising way forward [18, 20, 23, 26, 38, 39]. The work described here builds on this, demonstrating that a low cost device based on the principle of VOC analysis, which can be operated at the point of care (POC), is of potential use in IBS and IBD diagnosis and differentiation.…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…Previous work using sophisticated and expensive analytical equipment has shown that the VOC analysis approach for IBD and IBS diagnosis is a promising way forward [18, 20, 23, 26, 38, 39]. The work described here builds on this, demonstrating that a low cost device based on the principle of VOC analysis, which can be operated at the point of care (POC), is of potential use in IBS and IBD diagnosis and differentiation.…”
Section: Resultsmentioning
confidence: 84%
“…Changes in the composition of faeces, breath and other bodily fluids can be associated with disease states and can be reflected in the VOCs emitted from a sample [14,15,16,17]. Much work has been undertaken to investigate VOC analysis for gastro-intestinal disease diagnosis often using gas chromatography – mass spectrometry (GC-MS) or selected ion flow tube – mass spectrometry (SIFT-MS) [18,19, 20, 21,22, 23]. A summary of mass-spectrometry techniques for investigation of IBS and IBD can be found in a recent review [24].…”
Section: Introductionmentioning
confidence: 99%
“…A small quantitative study of urine samples [17] by our group found complete separation of active and inactive CD from controls (sensitivity: 100 and 77%, and specificity 100 and 81%, respectively, for each comparison), while a qualitative approach could separate CD from IBS cases (sensitivity: 87.5 and 94.4%, and specificity: 89 and 77%, respectively). The data for UC were less strong.…”
Section: Gas Chromatographic Analysis Of Possible Biomarkersmentioning
confidence: 98%
“…Based on current research, it has become apparent that the accurate reproducible detection of VOCs from biological samples has great potential to develop into a non-invasive diagnostic test for IBD. However, to date, there seems to be a limited number of published works investigating the VOCs present in the feces, in comparison to breath or urine, of IBD patients, compared to healthy donors [12,[14][15][16][17]. Human stool samples represent the end-product of diet, digestive and excretory processes, and colonic bacterial metabolism [6].…”
mentioning
confidence: 99%